Udvikling af diplomuddannelse i erhvervspædagogik på baggrund af resultater fra projekter [Developing diploma of vocational pedagogy based on results from projects] - Henriette Duch; Jeppe Egendal; Birgitte Marcussen; Christina Højlund; Ulla Nistrup (Nordic Journal of Vocational Education and Training, 2018)
In Denmark, it is mandatory for vocational teachers to complete Diploma of Vocational Pedagogy. The objectives of the diploma are defined by the rules and regulations for diplomas in general but it also has to support the national policy for vocational educations. Moreover, the diploma has to support the strategies and agendas of vocational colleges and vocational teachers. University colleges supply this diploma. University college teachers teaching in the programme have to develop their pedagogical and educational competencies in order to support these agendas. One way to explore the need for development of the programme is to participate in projects. Using Engeströms theory and methodology, the paper analyses how results from three research and development projects can form the basis for development of Diploma of Vocational Pedagogy. The analysis stresses the history and contradictions in each project seen from the perspectives of each teacher's subjectivity. The result is a method that can indicate how findings from projects can be used in the development of Diploma of Vocational Pedagogy.